Description of The Incident of Hypotension in Elderly Receiving Spinal Anesthesia at Cilacap Regional Hospital - Dilla Ainun Nurjanah; Martyarini Budi Setyawati; Wilis Sukmaningtyas (Viva Medika, 2023)
Spinal anesthesia is a type of regional anesthesia performed by injecting local anesthetic drugs into the subarachnoid space which can cause hypotension with an incidence of 16% - 33%. Hypotension is a drop in systolic blood pressure below 90mmHg. Risk factors that can increase the incidence of hypotension in spinal anesthesia include age. In young adults, hypotension is usually less severe than the elderly with the same high spinal anesthesia. The purpose of this study was to determine the picture of hypotension events in the elderly who received spinal anesthesia techniques at the Central Surgical Installation of Cilacap Hospital. The design of this study is quantitative descriptive with sampling using convenience sampling techniques. The study was conducted in June 2023. The sample of this study was elderly >60 years old totaling 52 respondents. The results of this study showed the incidence of hypotension as many as 38 respondents (67.3%) and not hypotension 17 respondents (32.7%). This study shows that the elderly are one of the factors in the incidence of post-spinal anesthesia hypotension.